DETERMINANT PRODUKSI KELAPA SAWIT: Studi Kasus Desa Catur Rahayu Kecamatan Dendang Kabupaten Tanjung Jabung Timur - Sandria, Wella; Yuvanda, Sesraria; Farida, Nur (Jurnal Development, 2021)
This study aim to find out and analyze the characteristics of oil palm farmers in the village of chess rahayu dendang sub-district, tanjung jabung timur district. To answer the purpose of the first research objective used descriptive analysis model and to answer the second research used multiple linear regression analysis model to obtain the information needeen then used survey research methods such as primary data with the number of respondents as many as 148 and secondary data. The result showed that the characteristics of oil palm farmers in rahayu chess village were on average male, the average age of farmers was 45-55 years, the average farmer graduated from elementary school, the average number of family dependents was 4 family dependents and the average experiance farming for 11 years. While the factors that influence palm oil production in the chess rahayu village are signifcant land area with a positive rate of 7,1%, significant positive use of fertilizer at 18,8% and significant positive plant life of 84,6%. Keywords: Factor Of Production, Characteristics Of Production, Oil Palm